An Analysis Of Organizational Culture, Work Environment And Leadership Style On Employee Performance At Auto 2000 Medan Pancing - Bima Satria; Emi Wakhyuni; Slamet Widodo (Sean Institute, 2024)
Organizational culture, work environment and leadership style on employee performance at Auto 2000 Medan Pancing. This type of research is a survey, while the research method is quantitative descriptive. This means that it is a research method that takes samples from a population and uses a questionnaire as a collection tool. In this research data and information were collected from respondents using questionnaires. After the data is obtained, the results are presented descriptively. The type of data used is primary data. Validation test R count X1 0.545. R count X1 0.831. R calculated Y 0.545. And the R table for the three variables is 0.204 and is declared valid. Reliability Test X1 0.648, X2 0.877, Y 0.653. Simple regression X1 0.325. X2 0.589. T test X1 5.121. X2 6.081 with a significance of 5%. Correlation and determination R 0.845 The test results of the correlation coefficient of determination or (R) show that organizational culture and leadership style have an influence on employee performance. This can be shown by the correlation coefficient value of R of 0.845. Meanwhile the test result value of the coefficient of determination or (R) is 69.7%. and the remaining 30.3% is influenced by other variables outside the research.